2000
DOI: 10.2298/jsc0004265m
|View full text |Cite
|
Sign up to set email alerts
|

The products of selenite hydrothermal treatment in lithium chloride solutions

Abstract: Selenite was boiled in LiCl solutions of different concentrations (1 M, 2 M, 3 M, 4 M and 5M) at the respective boiling temperatures and atmospheric pressure. The products were subjected to X-ray diffraction analysis, qualitative infrared analysis, differential thermal analysis, thermogravimetric analysis and microscopic examination. The product obtained in the 1 M LiCl solution was the ?-form of calcium sulphate hemihydrate (?-CaSO4.0.5H2O). In more concentrated LiCl solutons, 2M and 3 M, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 2 publications
1
8
0
Order By: Relevance
“…As for the KCl−CaSO 4 −H 2 O system, Li reported that pure α-HH could be prepared in KCl solution with or without additives. In contrast, Marinkovic and Kostic-Pulek showed that the product obtained in 1.0 M KCl solution was β-HH, and α-HH mixed with potassium pentacalcium sulfate monohydrate (goergeyite, Go) was the product in more concentrated KCl solution ((1.5 to 4) M). No explanation of the difference between their results was offered.…”
Section: Introductionmentioning
confidence: 99%
“…As for the KCl−CaSO 4 −H 2 O system, Li reported that pure α-HH could be prepared in KCl solution with or without additives. In contrast, Marinkovic and Kostic-Pulek showed that the product obtained in 1.0 M KCl solution was β-HH, and α-HH mixed with potassium pentacalcium sulfate monohydrate (goergeyite, Go) was the product in more concentrated KCl solution ((1.5 to 4) M). No explanation of the difference between their results was offered.…”
Section: Introductionmentioning
confidence: 99%
“…CaSO 0.5H O+1.5H O=CaSO 2H O   -CaSO 4 0.5H 2 O is produced by "wet process", e.g. by cooking of gypsum in a liquid medium at its temperature of boiling at atmospheric pressure, often in concentrated water salt solutions as 2M and 3M KCl (Marinković et al 1999) or 2M and 3M LiCl (Marinkovic et al 2000). This kind of hemihydrate is primary applicable in medicine and stomatology, but also it can be utilized in sculpture and for fine works in construction.…”
Section: Gypsummentioning
confidence: 99%
“…Therefore, an alternative approach for the preparation of α‐HH by the hydrothermal method has been suggested. This procedure involves the heating of gypsum in boiling or near‐boiling solutions of inorganic acids or their salts, such as H 2 SO 4 , KCl, CaCl 2 , and MgCl 2 9–12 , under atmospheric pressure.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, an alternative approach for the preparation of a-HH by the hydrothermal method has been suggested. This procedure involves the heating of gypsum in boiling or nearboiling solutions of inorganic acids or their salts, such as H 2 SO 4 , KCl, CaCl 2 , and MgCl 2 [9][10][11][12] , under atmospheric pressure. The dominant mechanism of a-HH formation by the hydrothermal method is a reaction of DH dissolution in the electrolytic solution, followed by crystallization (the so-called through-solution reaction mechanism).…”
Section: Introductionmentioning
confidence: 99%